Association between gastroesophageal reflux disease-questionnaire factors and gastroesophageal reflux disease incidence at Kardinah general hospital inpatient wards - Gosal, Darren; Santoso, Rachman Edi; Firmansyah, Yohanes (International Journal of Advances in Medicine, 2021)
Background: Gastroesophageal reflux disease (GERD) is a condition where an acid reflux into the esophagus with can resulted some symptoms. GERD is one of the most common disease in around the world. The most common symptom is heartburn, with its various risk factors. Diagnosing GERD based on the clinical examination or more advanced examination. One simple tool to help diagnosing is GERD questionnaire (GERD-Q). This study aims to find out the association of GERD-Q factors to GERD incidence at Kardinah inpatient wards. Methods: This study is cross sectional design, with the subjects are all patients in the inpatient wards, and asked with the Indonesian version of GERD-Q plus other questions. All data will be assessed with chi Square test. Results: Total of 84 respondents are in this study, where the relationship of each factors with GERD incidence are: gender (p value: 0.191), surgery (p value: 0.428), spicy foods consumption (p value: 0.920), fatty foods consumption (p value: 0.916), sour foods consumption (p value: 0.557), and irregular eating habit (p value: 0.023). Conclusions: Irregular eating habit is significantly associated with GERD incidence.